Financial sector reforms in the ASEAN economies in the 1980s : macromodelling of debt and twin deficits - Wan Latifah, W.M. (1994)
This thesis addresses issues of debt and the twin deficits - two serious ‘economic ills’. The central issue in this thesis (Part II) is on macromodelling of the twin deficits in an attempt to identify their determinants. This involves an investigation of the underlying theory and empirical evidence to show the workings of the links between debt and the twin deficits and between the twin deficits themselves. The usual practice in both theory and in empirical work, is to take the accounting identity and one or two other variables that are hypothesised to have effects on the twin deficits and posit causal linkages. We try to avoid this by building on the stylized facts on each of the macroeconomic aggregates and linking them to debt issues in building a full structural model of debt and the twin deficits. We arrive at a system of simultaneous equations, which none of the previous theory or empirical work has derived. We rename the deficit system of simultaneous equations which incorporates a debt identity and an output equation the `new twin deficits' model – signifying a departure from the conventional wisdom discussed in the literature survey.